An Integrated Approach using AHP-ER to Supplier Selection in Railway Projects. (2015) - Polat, Gul; Eray, Ekin
Abstract: Success in the construction projects can be simply described as finishing the construction work on time, within the budget and with the desired quality. Achieving the delivery of the right amount of materials on the right time and with the desired quality plays a critical role on the project success. Moreover, the cost of materials constitutes approximately 40% of the overall project budget. Therefore, selecting the right supplier for the right material is crucial. In the literature, there are several studies dealing with the supplier selection problem. These studies can be categorized into two main groups, which are; 1) the studies that aim to investigate the criteria that may be considered in the supplier selection process and to determine these criteria' importance levels, and 2) the studies that aim to propose various tools, methods and methodologies for selecting the right supplier. Each of these previous studies has considerably improved the supplier selection process. The aim of this study is to propose an integrated approach, which integrates analytic hierarchy process (AHP) and evidential reasoning (ER), to help construction companies in selecting the most appropriate supplier in their projects. In the proposed approach, the AHP method is used to find the weights of the selection criteria and the ER method is used to rank the alternative suppliers. The proposed approach is also applied to a problem of selecting the rail supplier for an intercity railway project in Saudi Arabia. In the case study, five different rail suppliers are ranked according to eight evaluation criteria by using the proposed approach. The findings revealed that the proposed approach can easily be employed by construction companies.